Misconception as barrier in understanding index and logarithm: the case of pre-tertiary education students / Wan Norliza Wan Bakar and Siti Farah Haryatie Mohd Kanafiah - Wan Bakar, Wan Norliza; Mohd Kanafiah, Siti Farah Haryatie (Unit Penerbitan UiTM Kelantan, 2020)
Misconception is an opinion that is wrong because it has been failure to understand the concept. Index and logarithm are the basic mathematical concept that is very important in advanced mathematics.It is being taught in the subject of additional mathematics at school level and refreshed again at university level. In Universiti Teknologi Mara Cawangan Kelantan (UiTMCK), index and logarithm is one of the topics in the subject of essential mathematics (MAT 037) . This research aims to explore and identify the misconception in understanding index and logarithm among pre diploma students. There were 120 pre diploma students taking Essential Mathematics on Semester September 2019 until January 2020 at UiTMCK involved in the diagnostic test. A set of diagnostic tests on the topic of index and logarithms developed by the experts were given to pre diploma students. The results revealed that the students do understand the topic of index and index equation very well. Unfortunately, when it comes to the topic of logarithm students became confused and the arrangement of BODMAS is not in appropriate order. Most of the students confused and they have their own interpretation in determine the meaning of variable.